PAYMENT SCHEME’S EFFECTIVENESS AMONG SELECTED PRIVATE HIGHER EDUCATION INSTITUTIONS IN NATIONAL CAPITAL REGION: BASIS FOR DEVELOPING STRATEGIC POLICY - Noriel Argarin Lastrollo; Jay A. Sario (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The COVID-19 pandemic boosted the utilization of online payment schemes or methods, which has been proven very beneficial. It kept the economy running as well as school operations. In particular, Higher Education Institutions (HEIs) adopted online payment transactions to allow students to proceed with enrollment. Yet, this abrupt change directly affected the students and parents especially on the use of online payment procedures in paying tuition fees. In this study, the researcher aimed to assess the effectiveness of online payment methods based on the following criteria: cost-efficient, safety, ease of use and speed. Also, the researcher wanted to investigate if there was a significant difference between the profile of the respondents and the effectiveness of online payment methods. Using cluster sampling, 1,050 students and 1,050 parents from selected cities in National Capital Region (NCR) namely, Manila City, Quezon City, and Taguig City, were recruited. Based on the results, the profile composition of parent respondents was, they were between 41 to 50 years of age, all females, with family monthly income of P30,001 to P45,000 and P45,000 to P60,000, college graduates, and preferred to use credit card and debit card. Furthermore, student respondents were mostly at the age of 19 to 20 years old, all females, in 4th year college, and preferred to use credit card and mobile payments. As to the assessment of online payment methods, most of the respondents perceived the online payment methods in terms of cost-efficiency, safety, and ease of use to be very effective. As to the challenges and issues experienced by students and parents on online payment methods, the following were identified: unfamiliarity, disorientation, difficulty in validation and problems with online applications. As to finding the significant difference between the age of respondents and the effectiveness of online payment methods, a significant difference between age groups and cost efficient, safety, ease of use, and speed was posited. As to finding the significant difference between sex of respondents and the effectiveness of online payment method, results revealed that there was a significant difference between sex and cost efficient, ease of use and speed. However, no significant difference was found between sex and safety. This study recommends that school administrators should provide orientation to new and old students regarding the use of online payment methods. They should make online tutorials on downloading and use of online applications available since it is critical for the student and parents to adapt online payment methods. The accounting and cashier should have a clear, simple and easy to follow procedure for online payment transaction. It is highly suggested also that the accounting office lessens the days of validating the payment made by the students and they must have a system for it. The school should promote online payment transaction as it saves them resources from filing payment receipts and using facilities. In addition, the social distancing should be encouraged to avoid the spread of COVID-19 virus. This study has significant implications on the management system implemented by the higher education institution.